2011
DOI: 10.1007/s00259-011-1793-1
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoscintigraphy and SPECT/CT using 99mTc filtered sulphur colloid in chylothorax

Abstract: We present a rare case of a chylothorax in a 60-year-old patient after resection of the thymus (myasthenia gravis and thymus hyperplasia). A left-sided chylothorax developed 20 days after the resection with an estimated daily fluid loss of 1.7 l.Chest lymphoscintigraphy was performed in the anterior and posterior position 60 min after injection of 4×74 MBq 99m Tc filtered sulphur colloid subcutaneously into the first interdigital space and the retromalleolar space of both feet. The images showed abnormal trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 3 publications
2
16
1
Order By: Relevance
“…Lymphoscintigraphy, which functionally assesses the lymphatic transport and regional lymph nodes, is an easy, non-invasive method for detecting abnormalities in the lymphatic system, including leakages such as chylothorax, chyloperitoneum and chyluria. Positive findings include tracer activity at the site where lymphatic fluid is accumulated, as seen in our case (20,21). ADT is the mainstay of treatment for patients with metastatic prostate cancer.…”
Section: Discussionsupporting
confidence: 66%
“…Lymphoscintigraphy, which functionally assesses the lymphatic transport and regional lymph nodes, is an easy, non-invasive method for detecting abnormalities in the lymphatic system, including leakages such as chylothorax, chyloperitoneum and chyluria. Positive findings include tracer activity at the site where lymphatic fluid is accumulated, as seen in our case (20,21). ADT is the mainstay of treatment for patients with metastatic prostate cancer.…”
Section: Discussionsupporting
confidence: 66%
“…13Y17 Baulieu et al 13 have reported on lymphoscintigraphy by the subcutaneous injection of 99m Tc-SC in which they could detect TD in 10 of the 30 patients with lower limb lymphedema and in 4 of the 7 patients with chylothorax and/or chyloperitoneum. There have also been a few case reports of such lymphoscintigraphy 14,15 employing SPECT/CT 16,17 for the purpose of localization of the leakage site in chylothorax. On the basis of these reports, lymphoscintigraphy by the subcutaneous injection of radiotracers seems to be useful in the localization of the leakage site in chylothorax and have a potential to visualize TD.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have already reported the usefulness of lymphoscintigraphy SPECT/CT for identifying the site of lymphatic leakage in adult patients with TD injuries. 18,19 Our case suggests that lymphoscintigraphy SPECT/CT is also suitable in pediatric patients presenting with chylothorax even when the amount of chyle leakage is minimal. In this neonate, the technique detected the site of lymphatic leakage, guiding the intranodal lymphangiography followed by TDE.…”
Section: Figurementioning
confidence: 99%